Mentoring and first line managers - Neugebauer, John (Henry Stewart Talks, 2019)
Mentoring, Benefits of having a mentor, Benefits of being a mentor, Benefits to the organisation, Company coherence, Organisational learning, How to find a mentor, Goals of mentor relationship, Ending a mentor relationship, Best practice for mentors, Mentoring exchange